Child-friendly Education in the Review of State Policy and Problematics of Children in Indonesia in Education - M.Syahran Jailani; Saidin Saidin; As’ad Isma (Universitas Muhammadiyah Enrekang, 2024)
Child-friendly education is education that provides a sense of security and comfort for children. The aim of this research is to analyze and describe state policies towards children's education in Indonesia, problems of children in Indonesia in education, and opportunities for children to grow and develop in modern society. This research approach uses a library study approach, in this research there is no research location because all data is taken through books and scientific journals. with documentation data collection techniques and data analysis techniques by reducing data, presenting data and verification. The results of this research found that state policy towards children's education in Indonesia was prepared through PPPA policy Number 8 of 2014 which regulates child-friendly education that can provide safe and comfortable education for students at school. The problems with education in Indonesia are limited technological knowledge, limited facilities and infrastructure, and limited experience. In today's modern era, many children are making the wrong use of technological developments, thus having several negative effects on children's physical and physical health